Country’s energy culture as a determinant of the “new European Union energy policy” - Pach-Gurgul, Agnieszka; Soliński, Bartosz (Journal of Public Governance, 2013)
The authors of the present article discuss the nature and priorities of the “new EU energy policy” and present various factors that determine it, especially a country’s energy culture. They define “energy culture” and describe its types in the European Union. In order to understand the role of energy culture in the establishment of the European Union’s “new energy policy”, the authors conduct statistical analyses using Ward and k-means methods. As a result, they divide EU countries into groups with similar energy cultures and with ways of adapting to the “new energy policy” of the EU, especially to environmental challenges, that are alike from the technological and economic point of view. Th e authors emphasize the role of public energy awareness and its effects in the context of fulfilling the requirements of the new EU energy policy.